THE SIGNIFICANCE OF ACADEMIC LITERACY IN ANALYSING TEXTS FOR TRANSLATION - Mujiyanto, Yan (Language Circle: Journal of Language and Literature, 2013)
Academic literacy has long been discussed throughout the scientific disciplines. Such discussions have partly resulted in a sort of awareness in peopleÃ¢â¬â¢s mind concerning how we implement it in the areas of scientific disciplines we deal with. In the translation domain, we question how much the significance of such stuff is for the benefit of comprehensively analyzing text for inter-language rendering. This paper intends to provide an answer to such question. It deals with the use of relevant literacy to analyze any source text as a basis to produce a target text through transfer of meaning and reconstruction of language fulfilling the aspects of readability, accuracy, and naturalness.